Introduction to dusty plasma physics - Shukla, P. K.; Mamun, A. A. (London: IOP Ang Book, 2002)
This book provides an excellent introduction to the fundamental physics of plasmas, which comprise most of the matter in the universe. It is based on lectures that were used for an introductory plasma course at the graduate level.
Bibliographical references 258-265p.; Index 266-270p.
Keywords: Dust crystals; Elongated dust grains; Plasma Physics; Physics